Adopting AI in Medan PR: a study of government reputation management - Purba, Arief Marizki; Lusia, Amelita (Faculty of Communications Science, Dr. Soetomo University, 2026)
This study examined how the Medan City Government adopts artificial intelligence in government public relations to strengthen reputation management through the lens of algorithmic governance and digital agility, while advancing an inclusivity-oriented civic branding narrative known as 'Medan Untuk Semua'. Using a qualitative case study design, data were collected through in-depth interviews, observation, and documentation. Informants were selected purposively from key internal actors responsible for policy direction, communication governance, and technical implementation, with limited snowballing applied to identify specialised technical personnel. Data analysis followed the Miles, Huberman, and Saldaña framework and was supported by NVivo-based coding and visualisation to map thematic relationships. The findings show that AI-driven Customer Relationship Management (CRM) systems, incorporating automated ticketing, predictive analytics for complaint classification, and integrated dashboards, together with the 'Medan Satu Data' ecosystem, operate as an institutional reputation architecture by enabling data-driven responsiveness, digital traceability, and cross-unit message consistency. AI also reshapes internal communication by orchestrating coordination among public relations units, social media administrators, and IT teams. However, the study identifies persistent tensions between speed and accuracy, uneven technological literacy across bureaucratic units, and the need for narrative sensitivity that algorithmic systems cannot fully automate. Overall, AI adoption in Medan illustrates a hybrid governance model in which technological infrastructure enhances service delivery and communication legitimacy, while human judgement remains essential for contextual interpretation, empathetic messaging, and reputational risk management. The study underscores the strategic value of integrating AI into local government communication systems to support inclusive and accountable public service delivery.